The participation of community health agents in a group of health education - Joyce Mazza Nunes; Eliany Nazaré Oliveira; Maria de Fátima Antero Sousa Machado; Patrícia Neyva Pinheiro da Costa; Neiva Francenely Cunha Vieira (Rev Rene)
Community health agents are the members of the Family Health Team that get closest to the families, as they often live in their community. Their action in the educational practice in health should be encouraged, due to their power to gather the subjects, motivating them to participate in community groups, and due to their knowledge about the local reality. In this study, three community health agents participated actively in health educational activities together with a group of women from a community in Fortaleza-CE, Brazil, from July to October 2009. We investigated the meaning of this experience to the community health agents, their opinions about the methodology used, identifying facilities, difficulties and limitations, looking for suggestions to improve the educational practice in the community. By expressing their opinions about the educational activities developed, they contributed to the improvement of this practice in the Family Health Strategy.